Percutaneous closure of congenital coronary artery fistulae in 5 children: A single center experience - Yadav, Shiv Kumar; Yi, Qi-jian (Asian Journal of Medical Sciences, 2014)
Background and Aim: Coronary artery fistulae (CAF) are rare anomalies. In this study, we have done percutaneous closure of CAF in children with three different devices; ventricle septal defect (VSD) occluder, patent ductus arterious (PDA) occluder and Cook coil. Materials and Methods: We retrospectively reviewed all patients, admitted to our heart center inpatient department between September 2004 and April 2013, that had a percutaneous closure of CAF in our center, and evaluated outcomes of patients with CAF treated with cardiac catheterization. Results: A total of fi ve patients (3 females) ranged in age from7 months to 10 years with congenital CAF underwent percutaneous closure. The fistulae had origins from right coronary artery (RCA) and from left coronary artery (LCA) in 3 cases and 2 cases respectively. One RCA drained to right atrium and rest four drained to right ventricle. All 5 cases had a co ntinuous murmur. During closure, 2 fistulae closed with VSD occluder, 2 with PDA occluder & 1 with Cook coil. Percutaneous closure was successfully achieved in all the 5 patients. Follow-up studies showed that there was complete abolition without recanalization. No deaths occurred. Conclusion: Percutaneous closure of congenital CAF is very safe and effective in children with less complication and shorter hospital stay. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11786 Asian Journal of Medical Sciences Vol.6(4) 2015 45-50